Kajian aspek ketahanan beberapa genotipe kedelai terhadap hama pengisap polong Riptortus linearis F. (Hemiptera : Alydidae) - SUHARSONO, SUHARSONO (Universitas Gadjah Mada, 2001)
The resistance of soybean to pod-sucking bug Ripforfus lineuris F. was studied using resistant genotypes selected from field and laboratory screening. The objective of the present study is to determine factors affecting the resistance of soybean to pod-sucking bug. The study was implemented in three major researches i.e. 1) to identi% the resistant genotype by selection in field and laboratory, 2 ) to study factors affecting the resistance mechanism, and 3 ) to study the effect of pod maturity and insect developmental stage and water stress ( wafer deficit) on degree of resistance. The ektend damage and number of stylet punctures on seed are the parameters of the resistance. The study showed that IAC-80-596-2 and IAC-100 genotypes were identified resistant to pod-sucking bug R. linearis as indicated by the damage on pod, seed and number of stylet punctures on seed consistently lower and unsuitable for host as compared to Wilis variety. The resistance was related to morphological aspects of soybean pod mainly pod pubescence, pod shell thickness, pod shell hardness, and chemically related to lower fructose of seed and higher fiber content in pod shell. No significant antibiosis was found. The seed damage had significantly positive correlation with fructose content (r = 0,60* ) and number of stylet punctures on seed ( r = 0,82*). The seed damage, however, negatively correlated to pod shell thickness (r = - 0,62*) and fiber content in pod shell (r = -0,67*). Path analysis showed that the resistance of IAC-596-2 and IAC-100 genotypes to pod-sucking bug was expressed i n morphological antixenosis due to thicker and higher fiber content i n pod shell, and lower fructose content. The seed damage at R6 pod developmental stage was more severe than those at R4 and R8. The damage intensity was not affected by insect developmental stage. Water stress (wufer deflcif) significantly affects the susceptibility of soybean to pod-sucking bug. I n susceptible variety, water stress increase the susceptibility to pod sucking bug. In resistant genotypes, however, the susceptibility is less affected by water stress. The relationship between podsucking bug resistant,genotype and water stress tolerance was unclear. I t was suggested that these genotypes possess some degrees of tolerance to water stress, therefore, further studies are needed. In the area with restricted water supply system, the use of resistant variety that tolerance to water stress is suggested.